Non-invasive assessment of intestinal permeability in healthy volunteers using transcutaneous fluorescence spectroscopy - Wei,J; Monfort,Sanchez E; Avery,J; Barbouti,O; Hoare,J; Ashrafian,H; Darzi,A; Thompson,A (Methods and Applications in Fluorescence, 2022)
The permeability of the intestinal barrier is altered in a multitude of gastrointestinal conditions such as Crohn's and coeliac disease. However, the clinical utility of gut permeability is currently limited due to a lack of reliable diagnostic tests. To address this issue, we report a novel technique for rapid, non-invasive measurement of gut permeability based on transcutaneous ('through-the-skin') fluorescence spectroscopy. In this approach, participants drink an oral dose of a fluorescent dye (fluorescein) and a fibre-optic fluorescence spectrometer is attached to the finger to detect permeation of the dye from the gut into the blood stream in a non-invasive manner. To validate this technique, clinical trial measurements were performed in 11 healthy participants. First, after 6 h of fasting, participants ingested 500 mg of fluorescein dissolved in 100 ml of water and fluorescence measurements were recorded at the fingertip over the following 3 h. All participants were invited back for a repeat study, this time ingesting the same solution but with 60 g of sugar added (known to transiently increase intestinal permeability). Results from the two study datasets (without and with sugar respectively) were analysed and compared using a number of analysis procedures. This included both manual and automated calculation of a series of parameters designed for assessment of gut permeability. Calculated values were compared using Student's T-tests, which demonstrated significant differences between the two datasets. Thus, transcutaneous fluorescence spectroscopy shows promise in non-invasively discriminating between two differing states of gut permeability, demonstrating potential for future clinical use.